Preliminary Clinical Experience with Shear Wave Dispersion Imaging for Liver Viscosity in Preoperative Diagnosis of Focal Liver Lesions - Dong, Yi; Qiu, Yijie; Zhang, Qi; Yang, Daohui; Yu, Lingyun; Wang, Wen-Ping; Dietrich, Christoph F. (Zeitschrift für Gastroenterologie, 2020)
Background The aim of our study is to analyze viscosity characteristics of focal liver lesions (FLLs) and the diagnostic performance of shear wave dispersion (SWD) in differentiating benign and malignant FLLs.Methods Between January 2018 and April 2018, 58 consecutive patients (median age 57, age range 21–74 years, 37 males) with 58 FLLs located on the right lobe of liver were prospectively studied. The Aplio i900 series diagnostic ultrasound system (Canon Medical systems) equipped with a curvilinear PV1-475BX transducer (1–8 MHz) was used. SWD slope and viscosity measurements were expressed as mean ± standard deviation for both liver tumors and background liver parenchyma. Histopathological results after surgery were regarded as the gold standard for diagnosis.Results Final diagnosis included 40 cases of malignant and 18 cases of benign FLLs. The mean viscosity value were 14.78 ± 1.86 m/s/kHz for hepatocellular carcinoma (n = 30), 14.81 ± 2.35 m/s/kHz for liver metastasis lesions (n = 10), 13.23 ± 1.31 m/s/kHz for hemangioma (n = 13), and 13.67 ± 2.72 m/s/kHz for focal nodular hyperplasia (n = 5). Malignant FLLs showed higher mean viscosity values (14.79 ± 3.15 m/s/KHz) than benign FLLs (13.36 ± 2.76 m/s/KHz) (p < 0.05). The best performing cut-off value of lesion viscosity was 13.15 m/s/kHz (sensitivity 83.3 %; specificity 56.5 %; area under the curve (AUC) 0.71) for malignancy) (p < 0.05).Conclusions The analysis of SWD slope and liver viscosity parameters provide additional viscoelastic information about FLLs before operation.
Keywords: shear wave dispersion; viscosity; ultrasound; diagnosis; focal liver lesions